Herding Behaviour in Sharia Stock: The Moderation Effect of Good Governance Business Sharia Disclosure - Ike Arisanti; Tri Wahyu Oktavendi (Journal of Accounting and Investment, 2020)
Research aims: One of the irrational behavior of investors is herding behavior. Disclosure of certain information is one of the triggering factors for herding behavior. However, “whether all the various types of information disclosure can encourage herding?” This is a big question related to the success of Good Governance Business Sharia (GGBS) information disclosure in stimulating herding behavior in Sharia stock trading. Hence, this study aims to examine the role of GGBS disclosure in herding behaviour.Design/Methodology/Approach: This study uses the object of companies listed on the ISSI (Indonesian Sharia Stock Index 2018. Data analysis in this research is using the Regression and moderation Test.Research findings: The results show that the GGBS disclosure was able to moderate herding behavior in Indonesian Sharia Stock. In this study it was found that the presence of GGBS Disclosure further strengthens the existence of herding behavior, meaning that investors conduct herding behavior reinforced by the information coming from within the company in the form of disclosure of GGBS Disclosure.Theoretical contribution/Originality: The theoretical impact is to expand the study of herding behavior and relate it to the disclosure of information. This study is also an initiator that examined the role of GGBS as moderating variable.Practitioner/Policy implication: The implication of this research is to be able to increase company concern in terms of GGBS disclosure so that the sharia stock market can be more transparent.Research limitation/Implication: This research only focuses on one information, namely GGBS Disclosure. This cannot generalize that information disclosure can strengthen or even weaken the existence of herding behavior. This research only uses one method of detection of herding, namely using Cross-Sectional Absolute Deviation (CSAD). This study uses all objects in the Indonesian Sharia Stock Index (ISSI) without considering sharia activities in each company.